Transfer Education in Southwest Border Community Colleges. Final Report of the Ford Southwest Transfer Education Research Project - Rendon, Laura I.; South Carolina Univ., Columbia. Coll. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The study described in this report examines both the positive and negative influences on student retention and transfer at six community colleges located along the U.S.-Mexico border. Chapter I reviews the literature on retention and transfer and establishes the conceptual framework and research objectives of the study. Chapter II offers baseline data on the six colleges, Southwestern College and Imperial Valley College in California, Arizona Western College and Cochise College in Arizona, and Laredo Junior College and Texas Southmost College in Texas. This section includes information on student enrollment by ethnicity and gender, associate degree recipients, transfers to senior institutions, type of information sent to and received from senior institutions, and faculty and counselor characteristics. Chapter III presents the results of site visits to the six community colleges and to two four-year colleges, focusing on the attitudes of community college staff concerning student achievement and transfer, internal and external barriers to minority student achievement, effective community college policies and practices, institutional monitoring of student flow and persistence, and relevant senior institution policies and practices. Chapter IV presents a profile of the students attending the six community colleges in terms of their background, educational commitments, social integration on campus, and predisposition to transfer. Chapter V examines the characteristics and attitudes of the community college faculty. Chapter VI reviews state-level policies and practices affecting student achievement and transfer in California, Arizona, and Texas. Finally, chapters VII and VIII discuss the findings and offer conclusions and recommendations. Survey instruments are appended. Included are 94 references. (AYC)
Sponsoring Agency: Ford Foundation, New York, NY.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Affirmative Action; College Faculty; College Transfer Students; Community Colleges; Educational Assessment; Enrollment Trends; Hispanic Americans; Minority Groups; Postsecondary Education; Program Effectiveness; School Policy; Student Characteristics; Teacher Attitudes; Teacher Characteristics; Transfer Programs; Two Year College Students; Two Year Colleges; United States (Southwest); Reports, Research; Tests/Questionnaires.